Ion‐Pairing of Phosphonium Salts in Solution: CH⋅⋅⋅Halogen and CH⋅⋅⋅π Hydrogen Bonds. Issue 43 (6th September 2013) - Ammer, Johannes; Nolte, Christoph; Karaghiosoff, Konstantin; Thallmair, Sebastian; Mayer, Peter; de Vivie‐Riedle, Regina; Mayr, Herbert
Abstract The 1H NMR chemical shifts of the C(α)H protons of arylmethyl triphenylphosphonium ions in CD2Cl2 solution strongly depend on the counteranions X−. The values for the benzhydryl derivatives Ph2CHPPh3+ X−, for example, range from δH=8.25 (X−=Cl−) over 6.23 (X−=BF4−) to 5.72 ppm (X−=BPh4−). Similar, albeit weaker, counterion‐induced shifts are observed for the ortho‐protons of all aryl groups. Concentration‐dependent NMR studies show that the large shifts result from the deshielding of the protons by the anions, which decreases in the order Cl− > Br− ≫ BF4− > SbF6−. For the less bulky derivatives PhCH2PPh3+ X−, we also find CH⋅⋅⋅Ph interactions between C(α)H and a phenyl group of the BPh4− anion, which result in upfield NMR chemical shifts of the C(α)H protons. These interactions could also be observed in crystals of (p‐CF3‐C6H4)CH2PPh3+ BPh4−. However, the dominant effects causing the counterion‐induced shifts in the NMR spectra are the CH⋅⋅⋅X− hydrogen bonds between the phosphonium ion and anions, in particular Cl− or Br−. This observation contradicts earlier interpretations which assigned these shifts predominantly to the ring current of the BPh4− anions. The concentration dependence of the 1H NMR chemical shifts allowed us to determine the dissociation constants of the phosphonium salts in CD2Cl2 solution. The cation–anion interactions increase with the acidity of the C(α)H protons and the basicity of the anion. The existence of CH⋅⋅⋅X− hydrogen bonds between the cations and anions is confirmed by quantum chemical calculations of the ion pair structures, as well as by X‐ray analyses of the crystals. The IR spectra of the Cl− and Br− salts in CD2Cl2 solution show strong red‐shifts of the CH stretch bands. The CH stretch bands of the tetrafluoroborate salt PhCH2PPh3+ BF4− in CD2Cl2, however, show a blue‐shift compared to the corresponding BPh4− salt.